WORK EXPERIENCE INTERNSHIP THROUGH THE EYES OF TECHNICAL UNIVERSITY STUDENTS (ON THE MATERIALS OF SOCIOLOGICAL RESEARCH) - Alexandr Yu. Myagkov; Maria V. Grigorieva; Irina V. Zhuravleva; Svetlana L. Zhuravleva (Russian State Vocational Pedagogical University, 2015)
The aim of the investigation is to study the problem of efficiency of work experience internship in a technical university and its role in the education of future professionals (problem has been investigated in the framework of the research project «Monitoring of social well-being and problems of professional adaptation of ISPEU students»).Methods. While carrying out of sociological research, selection of respondents was occurred on the multistage combined (serially-nested) model of sample among students I, III and V courses of six faculties of full-time course of ISPEU. The complex of questions (its answers show features of professional identity of the future experts on initial (I course), intermediate (III course) and finishing (V course) stages of their professional formation) has been developed to find out the dynamics of process of professional adaptation of students from the first to the fifth year. The information was processed with application of program and analytical complex SPSS. The comparative analysis to a gender sign of degree of satisfaction/dissatisfaction has been undertaken by the work experience internship organization on the side of high school and the accepting enterprises.Results. The level of graduates' satisfaction with the work experience internship is revealed that works on an estimation by students of quality of preparation in high school, the relation to a received speciality and success in the future profession. The data on a self-estimation of readiness of students to work experience internship is cited. Criteria of successful work experience internship are formulated.Scientific novelty. The given researches carried out by the authors, prove that work experience internship positively influences professional consciousness of students and promote formation of steady positive installations for professional job. However, work experience internship in its institutional forms is functional and appears to be the effective tool of professional socialisation of the future experts (it allows trainees to approve the knowledge received in high school in a practical field, and actual working conditions; to estimate own professional and personal potential; to adapt for the requirements shown by the future profession; to prove on a possible place of the future work), but in practice it turns out to have only theoretical positions of the organisation of educational process in high schools. The results show that a third of fifth-year students are not satisfied with the work experience internship organization by the university and host company actions, more than a quarter of students are not ready to practical work, 40% feel the clear lack of practical skills in their future profession. As a result, there is a commonplace opinion that internship is a waste of time. These data show that universities today have a reserve of unused potential to increase internship efficiency.Practical significance. The authors, based on the results of the survey, suggest the following ways to improve the practical training of future professionals (in order of priority). Firstly, it is necessary to increase the interest of employers in student practical work. Secondly, in the course of practice students should realize specific production targets relevant to their future profession, be engaged in real work, not just visit the company and certainly not distracted by extraneous work. It is necessary to increase the number of enterprises, institutions and organizations for student practical work, modify university theoretical courses, provide connection between theory and practice of real production and management, as well as increase time for work experience internship.